Estimasi Rugi Rugi Energi Pada Sistem Distribusi Radial 20 KV Dengan Metode Loss Factor Di Penyulang Lipat Kain Gi.Garuda Sakti - Dedek S Lumban Gaol; Firdaus Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
In this final project proposes the power loss estimation on 20 kV radial distribution feeders. Base on previous empirical approaches have been found by M.W. Gustafson by changing the coefficients and constants in a formula providing loss factor. In this research ,the calculation of power loss estimation is compared with power loss measurement. Power loss calculation uses ETAP software v.12.6.0 and loss factor method is applied as estimation method. Measurement result shows 2.969.834 kWh on 7,53% power loss in Lipat Kain feeder , Garuda Sakti substation , whereas the value obtained using the estimation method loss shows 2.919.236,491 kWh on 7,04 % . There is 50.597 kWh or 1,71 % different in power loss between measurement result and estimation. Key words: loss factor, daily load curve, , ETAP.